Epistemological foundations underpinning Howard Gardner's theory of multiple intelligences in pedagogy (Revista Innova Educación, 2019)
The Theory of Multiple Intelligences was proposed by the American Howard Gardner as a counterweight to the traditional paradigm of a single intelligence and has revolutionized the conception of intelligence in pedagogy. The objective was to determine the epistemological basis of Howard Gardner's theory of multiple intelligences in pedagogy. The study corresponds to the qualitative approach of the theoretical type of retrospective analysis for which hermeneutics has been used and as a technique the content analysis. The results and discussion of the research subsume a systematic theoretical interpretation of authors regarding the epistemological bases that support the theory of multiple intelligences in pedagogy. It is concluded that the epistemological bases of Howard Gardner's Theory of Multiple Intelligences are found in the humanistic psychology of education, neuropsychology and the holistic model of education.
Keywords: Education; Howard Gardner; multiple intelligences; pedagogy